Meningkatkan Digitalisasi UMKM di Udayana untuk Pertumbuhan Ekonomi Berkelanjutan - Mustafida, Mustafida; Putri, Alya Rasyida; Yolanda, Baiq Erwina; Ramadhani, Elsa Ayu; Ramdani, Fauzan Hari; Islami, Rendy Wahyu; Sazani, Asrofi; Kurnia, Agus (Universitas Mataram, 2025)
This community service program aims to enhance the understanding and skills of MSME actors in Udayana, Mataram in utilizing digitalization to improve competitiveness. Activities included socialization, technical training, direct mentoring, and evaluation. The training covered social media, e-commerce, and simple business management tools. Results showed a significant improvement in participants’ digital literacy and ability to apply digital tools for business operations and marketing. Market access also expanded with promising income growth. This program plays a crucial role in transforming MSMEs into professional, efficient, and adaptive businesses, supporting local economic development.